2019
DOI: 10.3390/ijms20092287
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Peripheral Neuropathy and Changes in Cytoskeleton

Abstract: Despite the different antineoplastic mechanisms of action, peripheral neurotoxicity induced by all chemotherapy drugs (anti-tubulin agents, platinum compounds, proteasome inhibitors, thalidomide) is associated with neuron morphological changes ascribable to cytoskeleton modifications. The “dying back” degeneration of distal terminals (sensory nerves) of dorsal root ganglia sensory neurons, observed in animal models, in in vitro cultures and biopsies of patients is the most evident hallmark of the perturbation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 189 publications
(213 reference statements)
0
28
0
Order By: Relevance
“…The finding of decreased peripheral nerve CSA is uncommon and has been reported in ALS and spinocerebellar ataxia syndrome . In vitro and animal studies have shown that the neurotoxicity of microtubule‐targeting agents (eg, taxanes) is predominantly due damage to the dorsal root ganglion (DRG) . This leads to axonal loss in the longest sensory nerves and contributes to the clinical symptoms consistent with a ganglionopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of decreased peripheral nerve CSA is uncommon and has been reported in ALS and spinocerebellar ataxia syndrome . In vitro and animal studies have shown that the neurotoxicity of microtubule‐targeting agents (eg, taxanes) is predominantly due damage to the dorsal root ganglion (DRG) . This leads to axonal loss in the longest sensory nerves and contributes to the clinical symptoms consistent with a ganglionopathy.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well accepted that the free nerve endings of primary sensory afferents, but also satellite cells, are susceptible to anticancer agents, such as BTZ and VCR, because of the lack of the blood–brain barrier and the presence of fenestrated capillaries, which lead to an unrestrained drug permeation ( 3 , 13 15 ). For this reason, in addition to in vivo animal models ( 55 ), numerous in vitro studies have been carried out, mainly on sensory neuron cultures, in order to investigate the molecular mechanisms at the basis of chemotherapy-induced neurotoxicity ( 36 , 52 ). Here, we used the adult DRG neuron in vitro model and the quantification of total neurite length as morphological read-out that correlates with neuron function and health ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the involvement of PK2 in murine in vivo CIPN models and the possible role of this protein as an insult-inducible endangering mediator, the aim of this study was to investigate whether PK2 may be involved in direct neurotoxicity induced by two different cytostatic drugs: VCR (microtubules formation inhibitor) and BTZ (26s proteasome inhibitor) on sensory neurons. Given the well-established alterations of neuronal cells following chemotherapy exposure (36)(37)(38)(39)(40)(41)(42)(43)(44)(45), we decided to use mouse primary sensory neuron cultures and evaluate the effects of PK-Rs antagonism on neurite outgrowth and immune mediator expression induced by VCR and BTZ.…”
Section: Introductionmentioning
confidence: 99%
“…Animal and human studies have demonstrated that the longterm use of the platinum derivatives [62,63] paclitaxel [64], vincristine [65], and bortezomib [66] can induce axonal degeneration, specifically, the loss of large myelinated, small unmyelinated and intra-epidermal nerve fibers. The loss of myelin and changes to the axonal cytoskeleton may alter the structure and impair the function of peripheral nerves, thus leading to the development of sensory and motor peripheral neuropathy and altered pain perception.…”
Section: Axonal Degenerationmentioning
confidence: 99%
“…The loss of myelin and changes to the axonal cytoskeleton may alter the structure and impair the function of peripheral nerves, thus leading to the development of sensory and motor peripheral neuropathy and altered pain perception. The molecular mechanisms of these phenomena are not fully established [43,63,67].…”
Section: Axonal Degenerationmentioning
confidence: 99%